Analysis of Sustainable Development 2008 report of PT Holcim indonesia Tbk Based on Indicator Protocols of Global Reporting Initiative and Key Performance Indicators of Cement Sustainability Initiative - Sukoharsono, Eko Ganis (The International Journal of Accounting and Business Society, 2009)
The  existence  of company  will  give  both  good  impact  and  bad  impact. For  the  good  impact,  company  can  be  a  tool  to  help  society  to  fulfill  their necessity.  In twentieth century, myriad of industrial company give bad impact on their existence.  They  don’t  care  with  natural  resources  they  use  to  provide something to  consumers  or don't consider employee,  environment,  consumers, or community as  significant thing to sustain their business.  The companies just take  natural  resources  as  many  as  they  need  to  process  for  their  economic activities  without  doing anything to  keep or make  renewable  natural  resources. As  for environment,  there are  many environmental  destruction  happening since the  companies  neglect  their  surroundings.  They only care for their own benefit. As a result, from the economic activities, companies provide externalities (Gray  et  al,  1996,  pg.  1)  -   consequences  of economic  activity  which  are  not reflected the cost borne by the individual or organization enjoying the benefit of the  activity)  as  impact  of  their  activities.  Many externalities make society affected by the impact.  Society  claims  to  get  the  companies  contribute  to surrounding  environment  where  the  companies  are  established.  Many cases show that the existence of company can make environmental destruction.  For example:  PT.  Lapindo  Brantas  on  their  case  of hot  mud.  The other cases are Newmont Minahasa Raya on Buyat Bay and PT.  Freeport on Papua.